Use of drug therapy and complementary therapy for glycemic control in adults with type 2 diabetes - Mancillas-Berrelleza, Luis Antonio (2025)
Many patients turn to complementary treatments (CT) when they do not see a positive result with the use of pharmacological treatments (PT) given by the physician for type 2 diabetes (T2D). Objectives: To determine the influence of the use of pharmacological and complementary treatment on glycemic control in adults with T2D. Methodology: The study design was correlational-descriptive. In adults with DT2 using TF (n=95) and TC (n=95). The glycated hemoglobin test was performed, the CTFA-5-DT2 questionnaire was used and the regulations of the general health law on research were adhered to. Results: A relationship was found in the use of TF and TC with glycemic control (rs .390, p= <0.01; rs= .275, p= <0.01). A multiple linear regression model was performed, showing a statistical significance of .003 (F= 3.12), an explained variance of 8.2% (R2= 0.82); the significant variables explained were marital status (β= .27, p= .001) and CT use (β= -2.63, p= .009). Conclusions: The use of TF and TC does influence glycemic control, people with DT2 using TC showed better glycemic control compared to those using only TF.